"Thinking on your feet"—a qualitative study of debriefing practice. Issue 1 (January 2016) - Krogh, Kristian; Bearman, Margaret; Nestel, Debra
Abstract Background Debriefing is a significant component of simulation-based education (SBE). Regardless of how and where immersive simulation is used to support learning, debriefing has a critical role to optimise learning outcomes. Although the literature describes different debriefing methods and approaches that constitute effective debriefing, there are discrepancies as to what is actually practised and how experts or experienced debriefers perceive and approach debriefing. This study sought to explore the self-reported practices of expert debriefers. Methods We used a qualitative approach to explore experts' debriefing practices. Peer-nominated expert debriefers who use immersive manikin-based simulations were identified in the healthcare simulation community across Australia. Twenty-four expert debriefers were purposively sampled to participate in semi-structured telephone interviews lasting 45–90 min. Interviews were transcribed and independently analysed using inductive thematic analysis. Results Codes emerging through the data analysis clustered into four major categories: (1)Values : ideas and beliefs representing the fundamental principles that underpinned interviewees' debriefing practices. (2)Artistry : debriefing practices which are dynamic and creative. (3)Techniques : the specific methods used by interviewees to promote a productive and safe learning environment. (4)Development : changes in interviewees' debriefing practices over time. Conclusions The "practice development triangle" inspired by the work of Handal and Lauvas offers a framework for our themes. A feature of the triangle is that thevalues of expert debriefers provide a foundation for associatedartistry andtechniques . This framework may provide a different emphasis for courses and programmes designed to support debriefing practices where microskill development is often privileged, especially those microskills associated withtechniques (plan of action, creating a safe environment, managing learning objectives, promoting learner reflection and co-debriefing). Across the levels in the practice development triangle, the importance of continuing professional development is acknowledged. Strengths and limitations of the study are noted.